Plasticity in food assimilation, retention time and coprophagy allow herbivorous cavies (Microcavia australis) to cope with low food quality in the Monte desert - Sassi, Paola Lorena (2010)
Energy balance depends on the efficiency with which organisms make use of their trophic resources, and has direct impact on their fitness. There are environmental variations that affect the availability as well as the quality of such resources; energy extraction also depends on the design of the digestive tract. It is expected that features associated with food utilization will be subjected to selective pressures and show some adjustment to the variability of the environment. Since energetic constraints challenge animals to display digestive compensatory mechanisms, the objective of this study is to determine the physiological and behavioral responses to spatial and seasonal heterogeneity in food quality. We investigated digestive strategies (digestive efficiency and coprophagy) in cavies inhabiting two different populations, and hence naturally experiencing different levels of diet quality. Cavies under experimentally different quality diets showed changes in dry matter digestibility and intake, digesta retention time and coprophagy. Our results partially support the expectations from theory and also reveal interpopulation differences in the ability to cope with changes in food quality, and may explain the capability of Microcavia australis to colonize extreme habitats.